Newsletter, Number 177 (NOVEMBER 1998) (American Research Center in Egypt, 2021)
CONTENTS: CREATING A FUTURE OUT OF THE PAST -- 9TH INT'L CONFERENCE -- DEVELOPMENT NEWS -- EXHIBITIONS -- A FELLOW AT WORK -- ERRATA -- HOLD THE DATE.